FRAMING ANALYSIS OF NICKEL MINING NEWS IN RAJA AMPAT: KOMPAS.COM AND CNN INDONESIA - Sasora, Fajar (Bajang Institute, 2025)
This study examines the framing analysis of news coverage on nickel mining in Raja Ampat by two Indonesian online media outlets: Kompas.com and CNN Indonesia. The research investigates how each platform constructs and presents news regarding the controversial nickel mining plans and operations in Raja Ampat, Southwest Papua. The unit of analysis consists of selected news articles published by CNN Indonesia and Kompas.com. These sources were chosen as primary data to understand the media’s role in shaping public perception. The nickel mining project in Raja Ampat has sparked widespread opposition from various sectors, including environmental activists, academics, tourism stakeholders, and religious leaders. This resistance is driven by concerns over the potential environmental degradation threatening both marine and terrestrial ecosystems in one of the world's biodiversity hotspots. Utilizing Robert Entman’s framing analysis method, the findings reveal that both media outlets acknowledge the mining project’s potential to harm ecological integrity and undermine sustainable tourism. However, CNN Indonesia emphasizes the role of the state in improving policy through strategic masterplan development, while Kompas.com highlights the need to evaluate mining permits, impose temporary halts on extractive operations, and strengthen community participation in protecting ecologically sensitive areas